Nucleotide sequence of the G protein gene of human respiratory syncytial virus reveals an unusual type of viral membrane protein. - Wertz, G W (1985)
The major surface glycoprotein (G) of human respiratory syncytial (RS) virus has an estimated mature Mr of 84,000-90,000. Among a library of cDNA clones prepared from RS virus mRNAs, we identified clones that hybridized to a message that encoded a Mr 36,000 polypeptide that was specifically immunoprecipitated with anti-G antiserum. The amino acid sequence of the G protein backbone was determined by nucleotide sequence analysis of several of the cDNA clones. It contains a combination of structural features that make it unique among the known viral glycoproteins. The G mRNA is 918 nucleotides long and contains a single major open reading frame that encodes a polypeptide having 298 amino acid residues with a Mr of 32,587, a finding consistent with the Mr 36,000 estimate for the in vitro translation product of the G mRNA. This suggests that greater than 50% of the molecular weight of the mature glycoprotein may be contributed by carbohydrate. Glycosylation of G is largely resistant to tunicamycin, an inhibitor of the attachment of N-linked oligosaccharides, suggesting that the majority of the carbohydrate residues are attached via O-glycosidic bonds. In accordance with this, serine and threonine residues, the acceptor sites for O-linked oligosaccharides, comprise 30.6% of the total amino acid composition. There are also four potential acceptor sites for N-linked oligosaccharides. The amino acid sequence lacks both an NH2-terminal hydrophobic signal sequence and a COOH-terminal hydrophobic region. Instead, a strongly hydrophobic region is located between amino acid residues 38 and 66. This region may serve as both the signal to insert the nascent polypeptide through the membrane and as the membrane anchor site.